Heavy metals in agricultural soils of the Llallimayo sub-basin, department of Puno - Espinoza_Rivas, Germán R. (2022)
Contamination of aquatic environments by heavy metals is one of the major concerns in rural localities and urban cities, for this reason during the months of July and November 2020, parameters were evaluated and samples were taken upstream and downstream of the Chacapalca river, analyzing physicochemical parameters: such as hydrogen potential (pH), temperature (°C), electrical conductivity (EC); heavy metals: aluminum (Al), arsenic (As), cadmium (Cd), total chromium (Cr), copper (Cu), iron (Fe), manganese (Mn), mercury (Hg), lead (Pb), zinc (Zn); total coliforms and thermotolerant coliforms. The objective was to evaluate water quality in the Llallimayo River sub-basin and identify the pollutant factors correlated with the water ECAs of D.S. N° 004-2017-MINAM. The inorganic parameters indicate that high values of pH (9.7) and EC (2674) exceed the ECA values; likewise, the inorganic parameters show that the elements Al, As, Cd, Cu, Mn, Hg and Pb, are not suitable for vegetable irrigation, animal drinking and aquatic environment quality. In conclusion, the discharge of mining effluent seriously contaminates and exceeds the permissible limits for Al, As, Cu, Fe, Mn and Zn in water for human use and consumption.